Identification of algD and oprL genes in Pseudomonas aeruginosa isolated from multiple environments and different local sources in Iraq (Kuwait Journal of Science)
The aim of this study was to investigate the spread of the genes algD and oprL in P. aeruginosa within the genetic structure of environmental sources of isolates and various clinical studies, and to evaluate a successful alternative for diagnosing Pseudomonas aeruginosa (P. aeruginosa) among various sources. In this study, 100 samples were collected from various clinical and environmental sources. Twenty-eight isolates of P. aeruginosa bacteria were isolated. Nine pathological samples were taken from wounds, burns, blood, and ear infections in three governorates: Salah al-Din, Baghdad, and Kirkuk. Five isolates of P. aeruginosa bacteria were collected from contaminated water from the Salah Al-Din and Baghdad governorates. The isolates were diagnosed phenotypically through the colony's shape, colour, odour and interaction with Gram stain. Additionally, the VITEK 2 system was used to confirm the diagnosis of the isolates. The results show that all the isolates belonged to the bacteria P. aeruginosa. The results of the molecular diagnosis using a polymerase chain reaction (PCR) technique for three genes with specialised primers (16SrRNA, algD, and oprL) show that most of the bacterial isolates from different sources belong to the type P. aeruginosa because they contain the specific gene 16SrRNA except for five isolates (M5, M7, M8, M9 and W1). Four of these belong to isolates with a pathogenic source and one was isolated from water. The results of the PCR for the algD gene show that all isolates contain the gene except for four diseased samples. Samples M5, M7, M8, and M9 were without the gene, while all isolates had the oprL gene. A sequencing analysis of the DNA was then performed for the isolates that were not associated with the specialised primers of the above genes to ensure their genera (M5, M7, M8, and M9), in addition to a sample of 15 isolated from soil (S6) that was associated with all special primers for the same genes for the purpose of comparison. The results show that isolates M5, M7, M8 and M9 were diseased isolates belonging to Escherichia coli, while the 15 isolated from soil (S6) were diagnosed as P. aeruginosa. © 2024 The Authors